Model matematika pengeringan daun bunga kecombrang (etlingera elatior jack) pada pengering rotary skala laboratorium - Melvin Emil Simanjuntak; Paini Sri Widyawati (AGROINTEK, 2022)
Ginger torch (Etlingera elatior Jack) is an herbaceous plant that is used as a flavoring, deodorizing, anti-oxidant, and antimicrobial. The fresh ginger torch has a high moisture content so that it can’t be stored for a long time because it will rot quickly. Drying is needed to preserve the ginger torch so that it can last longer. The research was aimed to determine the mathematical model, effective moisture diffusion, and activation energy for drying the leaves of Etlingera elatior Jack on a rotary dryer. The method used in this research was an experiment with three times repeated then followed by data analysis with curve expert 2.3.0 and MS-excel software. This research was performed by using a rotary dryer at temperatures of 60 oC, 70 oC, 80 oC, and 90 oC. The ginger torch was chopped about 1 cm, with a mass of 400 grams for each sample. Measurement of moisture content was carried out every 20 minutes. The results showed that the most suitable drying model was the Rational model with the general form of